2017
DOI: 10.21077/ijf.2017.64.1.60074-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary incorporation of fish/prawn meal on performance of Catla catla (Hamilton) during nursery phase

Abstract: Nursery evaluation of catla spawn was carried out by feeding three iso-nitrogenous diets (35% protein in raw and cooked form) for a period of 30 days. The three test diets (treatments) in raw form were: T1 -groundnut oil cake (GOC) + rice bran (RB) + vitamin-mineral (V-M) premix; T2 -GOC+RB+fish meal (FM) + V-M premix, T3 -GOC+RB+prawn meal (PM)+V-M premix. The diet groups GT1, GT2 and GT3 respectively were same feed combinations in cooked form. Incorporation of prawn meal as animal protein source led to signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…pH below 7 negatively afects the nitrifcation rate and the growth of the cultured species [46,47]. Te average pH was in the suitable range (7.40-7.70) as reported in earlier studies for nursery rearing of spawn in indoor systems [6] except for reduced pH and alkalinity in a higher stocking density, which might have afected the survival and growth of spawn in the experimental units due to acid stress as the pH efect is related to age and development, and larval stages are most sensitive to pH changes [48,49]. Te increase in heterotrophic bacteria increases acid production through the nitrifcation process and consumes alkalinity in the intensive biofoc system which reduced total alkalinity with the increased C/N ratio and stocking density [50].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…pH below 7 negatively afects the nitrifcation rate and the growth of the cultured species [46,47]. Te average pH was in the suitable range (7.40-7.70) as reported in earlier studies for nursery rearing of spawn in indoor systems [6] except for reduced pH and alkalinity in a higher stocking density, which might have afected the survival and growth of spawn in the experimental units due to acid stress as the pH efect is related to age and development, and larval stages are most sensitive to pH changes [48,49]. Te increase in heterotrophic bacteria increases acid production through the nitrifcation process and consumes alkalinity in the intensive biofoc system which reduced total alkalinity with the increased C/N ratio and stocking density [50].…”
Section: Discussionsupporting
confidence: 68%
“…In India, Indian major carps account for 87 percent of the country's total freshwater aquaculture production [3]. Hatchery-produced seed meets demand, but hatcheries are more concerned with quantity than quality, and the spawn-to-fry yield ratio of these species is 3 : 1 in earthen ponds, with catla fry performance always being lower in terms of growth and survival [4][5][6]. Fish in the nursery stage are also often subjected to intensifcation which generally increases stress and subsequently susceptibility to infectious disease, hence requiring proper management to obtain optimum growth and survival [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, Das et al (2015) observed similar growth performance for fry fed at 75 and 100% of the above mentioned ration and recommended the former, thereby saving good amount of supplementary feed. Similar attempts have also been made over the years to modify use of various other inputs to refine the carp seed production technology (Jena et al, 1998;Das et al, 2015;Kamble et al, 2017). Apart from fertilisation and supplementary feeding, depth of water in nursery also plays a significant role on the growth performance of the fry.…”
mentioning
confidence: 94%